3-6(-3+x)=-16-4x

Simple and best practice solution for 3-6(-3+x)=-16-4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3-6(-3+x)=-16-4x equation:



3-6(-3+x)=-16-4x
We move all terms to the left:
3-6(-3+x)-(-16-4x)=0
We add all the numbers together, and all the variables
-6(x-3)-(-4x-16)+3=0
We multiply parentheses
-6x-(-4x-16)+18+3=0
We get rid of parentheses
-6x+4x+16+18+3=0
We add all the numbers together, and all the variables
-2x+37=0
We move all terms containing x to the left, all other terms to the right
-2x=-37
x=-37/-2
x=18+1/2

See similar equations:

| 250-50g=100 | | n/4+17=20 | | 3x-2=-2x+-4 | | j+(-97)=-22 | | 3(g+2)/2=9 | | 7x-14=-29 | | 2-(-10-4)=-8q+-10q | | 4(x+`1)=4(2-x) | | x=3/2x+14 | | (2x-12)+(9x-26)=(4x+43) | | 3x²+12-15=0 | | 3x-17-5x=19 | | -7x-5+11-9=-12 | | 1.2b=−1.44 | | -7x-5+11x-9=12 | | a+5=-5a+13 | | 6x-1+10x-11=180 | | (5y+2)=15y | | 1x+35=2x+30 | | 5=7-2x+2x | | Y=x-101 | | 3(5y+2)=157 | | 5(x+20)=7-+30 | | -3a2=27;a=3 | | ½(8x–6)=25 | | 48=p-6 | | -7x-5+11-9=12 | | 5x-9+12=-10 | | 2x+6=4x-3=5x+12 | | 5x-9+12=10 | | 2(4/3(b-7))+5=21 | | y/3+2=41 |

Equations solver categories